The Driving Factors of Transaction Behavior for Shoe Cleaning Services Through Social Commerce Platforms - Purnama Sari, Desak Made Febri; Putra Budiartha, I Putu Abdi; Oka Martini, Ida Ayu; Paramita Pika, Putu Ayu Titha (Jurnal Ekonomi dan Bisnis Jagaditha, 2025)
This study discusses the phenomenon of the increasing use of social commerce platforms, such as Instagram, by shoe cleaning service providers to promote and sell their services. The trend shows that more consumers are shifting from traditional methods to digital platforms to search for services and conduct transactions. Therefore, this study aims to identify the factors driving transaction behavior for shoe cleaning services through social commerce platforms like Instagram. The research method used is quantitative data analysis involving 314 consumers who made transactions at nine shoe cleaning service brands in Bali province. The data were analyzed using Confirmatory Factor Analysis (CFA) in the SPSS version 25 program. The results of the data analysis indicate that from the 36 indicators initially tested, four main factors were identified that explain the drivers of transaction behavior for shoe cleaning services through social commerce platforms, namely "Channel Service Integration, Application Usability, Virtual Environment, and Omnichannel Marketing." The findings suggest that these factors play a significant role in driving transaction behavior for shoe cleaning services through social commerce platforms. Therefore, these factors can serve as a foundation to optimize marketing strategies and services for shoe cleaning service providers.